Automatic Tamoto Crop Disease Prediction System by Using the Deep Learning Approach - Mr. Sri Vishnu Neerubai, Prof. G. Anjan Babu (Mathematical Statistician and Engineering Applications, 2022)
Agriculture is a major requirement for humans in all over the world. It plays a major role in the food commodities. Most of the famers face a lot of loss due to the agricultural crop diseases. Here particularly focused on the tomato crop diseases that may occur due to the climatic conditions are various other factors. Here the deep convolution neural network is used to detect the diseased crop with the dieses name by classifying the healthy and diseased tomato crop plants automatically from the data that collected from crops by using the Agri-electronic device. With this the diseases can be detected in early stage so that the yielding of the crops can be improved. The results have achieved the effective detection accuracy.